Light Emitting Diodes Photobiomodulation Improves Cardiac Function by Promoting ATP Synthesis in Mice With Heart Failure - Zhang, Wenwen; Gao, Xinlu; Wang, Xiuxiu; Li, Desheng; Zhao, Yiming; Zhang, Tingting; Ne, Jingwen; Xu, Binbin; Li, Shuainan; Jiang, Zuke; Sun, Hongyue; Ma, Wenya; et al. (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is the common consequences of various cardiovascular diseases, often leading to severe cardiac output deficits with a high morbidity and mortality. In recent years, light emitting diodes-based therapy (LEDT) has been widely used in multiple cardiac diseases, while its modulatory effects on cardiac function with HF still remain unclear. Therefore, the objective of this study was to investigate the effects of LED-Red irradiation on cardiac function in mice with HF and to reveal its mechanisms. In this study, we constructed a mouse model of HF. We found that LED-Red (630 nm) was an effective wavelength for the treatment of HF. Meanwhile, the application of LED-Red therapy to treat HF mice improved cardiac function, ameliorate heart morphology, reduced pulmonary edema, as well as inhibited collagen deposition. Moreover, LED-Red therapy attenuated the extent of perivascular fibrosis. Besides, LED-Red irradiation promoted calcium transients in cardiomyocytes as well as upregulated ATP synthesis, which may have positive implications for contractile function in mice with HF. Collectively, we identified that LED-Red exerts beneficial effects on cardiac function in HF mice possibly by promoting the synthesis of ATP.